2011
DOI: 10.1590/s1519-38292011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Acompanhamento de recém-nascidos de baixo peso pela atenção básica na perspectiva das Equipes de Saúde da Família

Abstract: Objectives: to examine the perceptions and practices of Family Health Teams (FHTs) regarding the basic care (BC) follow-up of underweight newborns (UWNBs).Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Qualitative studies have indicated that the use of pacifiers is correlated with cultural issues, maternal uncertainty about her ability to breastfeed, and crying and behavior of baby. 3 , 16 , 23 , 24 Previous studies have indicated that infant-related factors that favor the use of bottle feeding include decreased weight gain, excessive crying, 12 the use of pacifiers, 6 and the consumption of processed milk, tea, and water. 6 Maternal-related factors that favor the use of bottle feeding include teenage mothers, 6 maternal uncertainty about her ability to breastfeed and difficulty in breastfeeding, 6 , 12 , 23 nervousness and impatience, 12 convenience, 12 working outside the home, 12 , 13 and coexistence with the maternal grandmother.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies have indicated that the use of pacifiers is correlated with cultural issues, maternal uncertainty about her ability to breastfeed, and crying and behavior of baby. 3 , 16 , 23 , 24 Previous studies have indicated that infant-related factors that favor the use of bottle feeding include decreased weight gain, excessive crying, 12 the use of pacifiers, 6 and the consumption of processed milk, tea, and water. 6 Maternal-related factors that favor the use of bottle feeding include teenage mothers, 6 maternal uncertainty about her ability to breastfeed and difficulty in breastfeeding, 6 , 12 , 23 nervousness and impatience, 12 convenience, 12 working outside the home, 12 , 13 and coexistence with the maternal grandmother.…”
Section: Introductionmentioning
confidence: 99%
“…This deficiency was noticed by health professionals of Pirituba and Perus, in the northern area of São Paulo, when they warned of the non-compliance with guidelines on care for babies at risk regarding underweight newborn babies. 25 The data used to evaluate the work process were collected from the CC/CSC. Thus, when this information is interpreted, it is necessary to take into account the possible differences between these records and those available in the USBFs, as it is also necessary to consider the number of mothers who forget to take the CC/CSC with them to the consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Sendo os mais prevalentes: políticos, gerenciais, institucionais e estruturais. Em relação aos fatores políticos e gerenciais destaca-se a insuficiência de recursos para a saúde e para o cuidado à criança na ABS, a falta de insumos, em especial, de medicamentos, assim como os aspectos relativos à inadequação na estrutura física das unidades de saúde (BUCCINI et al, 2011). É de suma importância destacar que o controle social é um aspecto com grande potencial ao que diz respeito em garantir a disposição de recursos materiais e garantir o acesso.…”
Section: Categoria 2 -Carência De Recursos Materiais E Dificuldades Nunclassified